HUBUNGAN TINGKAT PENGETAHUAN IBU HAMIL DENGAN STATUS GIZI SELAMA KEHAMILAN DI PUSKESMAS TOMPASOBARU KABUPATEN MINAHASA SELATAN - Tumangen, Yachika; Purwati, Anik (NHM PRESS, 2024)
Background: One of the factors that causes pregnant women to experience deficient nutritional status in pregnant women is the lack of knowledge of pregnant women in determining good nutrition during pregnancy. Objective: to find out whether there is a relationship between the level of knowledge of pregnant women and nutritional status during pregnancy at the Tompasobaru Community Health Center, South Minahasa Regency. Method: This research uses analytical observational research with a cross sectional research design. A sample of 15 was taken using the accidental sampling technique, which is a sampling technique based on the large number of samples found during observation for a specific purpose. This research was conducted in May 2024. Results: From the level of knowledge, the majority of respondents with good knowledge were 7 respondents (46.7%) and the majority had normal nutritional status in pregnant women, 11 respondents (73.3%). From the statistical test using Chi-square which was carried out with the help of SPSS for Windows software, the p value was 0.004 so that the relationship between the level of knowledge of pregnant women about nutrition and the nutritional status of pregnant women was significant. Conclusion: There is a relationship between knowledge about nutrition and the nutritional status of pregnant women at the Tumpasobaru Community Health Center, South Minahasa Regency with a p value of 0.004